AUTHOR AND TRANSLATOR: THE PROBLEM OF MUTUAL UNDERSTANDING - Umirziyaev Umidjon Makhamadjonovich; Rakhmonova Madinakhon Ilkhomjonovna (Web of Journals Publishing, 2025)
Knowing the characteristics of both languages implies thoroughly studying the original text, working on its vocabulary and cultural references, which is very important for the translator. This also, to some extent, requires the translator to be a scholar and a researcher.
Keywords: Intuition, imagination, emotion, subtlety